Cardiac and respiratory monitoring in the NICU and PICU - Bellsham-Revell, Hannah (Henry Stewart Talks, 2025)
Cardiac and respiratory monitoring, Continuous invasive and non-invasive monitoring, Guidelines for weaning off care, Ethical considerations in the ICU